Method for preparing copper sulfate pentahydrate crystal by using copper-rich slag

Through high-temperature ventilation, pressurized oxidation, acid leaching, evaporation, cooling and crystallization, microwave drying, the problems of high energy consumption and low equipment utilization of copper slag in the existing technology are solved, and the five high-efficiency and low-cost Preparation of water copper sulfate, the product quality meets industry standards.

CN119191334APending Publication Date: 2024-12-27NANCHANG CAMPUS OF JIANGXI UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411405145.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the method for preparing copper sulfate of copper rich slag has problems such as high calcination temperature, long time consumption, large energy consumption, low equipment utilization rate and high production cost.

Method used

Using high-temperature ventilation pressurized oxidation-acid leaching-evaporation-cooling crystallization-microwave drying, copper-rich slag is added to sulfuric acid solution for acid leaching reaction, and ripe lime is added to remove impurities after pressurization and cooling, and the evaporation and cooling process are controlled to obtain Copper sulfate pentahydrate crystal.

Benefits of technology

It has achieved the preparation of copper sulfate pentahydrate with short time consumption, low energy consumption, high equipment utilization rate and low production cost, and no wastewater production, and the product quality meets the industry standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191334A_ABST
    Figure CN119191334A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal smelting, in particular to a method for preparing copper sulfate pentahydrate crystals from copper-rich slag. The method comprises the following steps: adding the copper-rich slag into a sulfuric acid solution, pressurizing, carrying out an acid leaching reaction, cooling, and carrying out suction filtration to obtain a filtrate; slaked lime is added into the filtrate, and a leaching solution is obtained through separation; and evaporating the leachate, then carrying out cooling crystallization and centrifugal separation, and carrying out microwave drying on the precipitate obtained by centrifugal separation to obtain the copper sulfate pentahydrate crystal. The method has the advantages of short time consumption, low process energy consumption, no wastewater generation, high equipment utilization rate, high product yield, low production cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal smelting, and in particular to a method for preparing copper sulfate pentahydrate crystals by utilizing copper-rich slag. Background Art

[0002] Copper sulfate pentahydrate, commonly known as blue vitriol, gall vitriol or copper vitriol, is a blue crystal that is widely used in many fields such as industry, agriculture, medical treatment, chemical analysis, crystallographic research, etc. It is very stable at room temperature and pressure. Copper-rich slag is a by-product produced during the smelting process of non-ferrous metal smelting enterprises. In addition to being rich in copper, copper-rich slag also contains valuable metals such as lead, silver, antimony, and gold. Copper-rich slag is often used in industry to directly produce copper sulfate, which has greater profits and better benefits than the output of crude copper. At present, the treatment methods for producing copper sulfate with copper-rich slag (including sponge copper) mainly adopt roasting-leaching-impurity removal-filtration-evaporation-concentration-crystallization method and air direct oxidation-sulfuric acid leaching method. The former adopts roasting above 700°C, which has high roasting energy consumption, large equipment investment, and is easy to produce harmful gases. The air direct oxidation method mainly uses oxygen in the air to oxidize metallic copper under normal pressure. The oxidation time takes 7 to 8 hours, which is time-consuming, resulting in high energy consumption, low equipment utilization, and high production cost.

[0003] Therefore, a method for preparing copper sulfate pentahydrate crystals using copper-rich slag is provided to overcome the shortcomings of the existing technology for preparing copper sulfate using copper-rich slag, such as high roasting temperature, long time consumption, high energy consumption, low equipment utilization rate and high production cost, which is of great significance to the field of metal smelting technology. Summary of the invention

[0004] Based on the above content, the present invention provides a method for preparing copper sulfate pentahydrate crystals using copper-rich slag.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a method for preparing copper sulfate pentahydrate crystals using copper-rich slag, comprising the following steps:

[0007] The copper-rich slag is added to a sulfuric acid solution and pressurized to carry out an acid leaching reaction, and then the temperature is reduced and filtered to obtain a filtrate;

[0008] adding slaked lime to the filtrate to separate and obtain a leachate;

[0009] The leachate is evaporated, cooled and crystallized, and centrifuged. The precipitate obtained by centrifugation is microwave dried to obtain the copper sulfate pentahydrate crystals.

[0010] In a preferred embodiment of the present invention, the copper-rich slag is a by-product produced during the non-ferrous metal smelting process.

[0011] In a preferred embodiment of the present invention, the mass concentration of the sulfuric acid solution is 15%-30%; the mass ratio of the sulfuric acid solution to the copper-rich slag is (2-4):1; the pressurization is specifically to introduce air to pressurize 0.5-1.0MPa; the temperature of the acid leaching reaction is 200-300°C, and the time is 20-40min.

[0012] If the concentration of the sulfuric acid solution is lower than the above range, the leaching rate of copper will be too low, and if it is higher than the above range, the acidity will increase, which will lead to excessive acidity of the crystalline copper sulfate product. Therefore, the concentration of the sulfuric acid solution is preferably limited to the above parameter range.

[0013] In a preferred embodiment of the present invention, the cooling is specifically cooling by circulating cooling water; the leached residue obtained after the suction filtration is further recovered and processed.

[0014] In a preferred embodiment of the present invention, the amount of slaked lime added is such that the pH of the filtrate is 4.0-5.0.

[0015] When the pH of the filtrate exceeds the above parameter range, copper ions will form copper hydroxide precipitation and the yield of copper sulfate pentahydrate crystals will be reduced.

[0016] In a preferred embodiment of the present invention, the specific gravity of the leaching solution is controlled to be 1.6-1.8 g / cm by evaporation. 3 , so that the solubility of copper ions in the solution reaches saturation and there is no need to repeat the cycle of evaporation and cooling crystallization; the cooling crystallization is specifically cooled to room temperature by circulating cooling water.

[0017] A second technical solution of the present invention is a copper sulfate pentahydrate crystal prepared according to the above method.

[0018] A third technical solution of the present invention is the application of the above copper sulfate pentahydrate crystals in the industrial field, agricultural field or chemical analysis field.

[0019] The present invention discloses the following technical effects:

[0020] The invention provides a method for preparing copper sulfate pentahydrate crystals by using copper-rich slag. The method has the advantages of short time consumption, low process energy consumption, no waste water generation, high equipment utilization rate, high product output, low production cost, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The present invention is a process flow chart for preparing copper sulfate pentahydrate crystals using copper-rich slag. DETAILED DESCRIPTION

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0028] The "room temperature" described in the present invention, unless otherwise specified, refers to 20-30°C.

[0029] A first aspect of the present invention provides a method for preparing copper sulfate pentahydrate crystals using copper-rich slag, comprising the following steps:

[0030] Step 1, high temperature ventilation pressurized oxidation acid leaching: crush the copper-rich slag and add sulfuric acid solution to dissolve it, the mass ratio of sulfuric acid solution to copper-rich slag is (2-4):1, and air is introduced and pressurized; the solution temperature is 200-300°C, the pressurized pressure is 0.5-1.0MPa, and the acid leaching reaction is 20-40min to make the metal Cu 2+ 、Zn 2+ 、Part of Cd 2+ , Fe 3+ , Fe 2+ 、Co 2+ , Sb 3+ , part Bi 3+ , Ca 2+ The plasma enters the sulfuric acid solution.

[0031] Step 2, filtration: After the acid leaching reaction in step 1, use external circulating cooling water to cool and filter, and then use a vacuum pump to vacuum filter to obtain a purified filtrate.

[0032] Step 3, impurity removal: add slaked lime to the above filtrate, adjust the pH to 4.0-5.0, and make Fe 3+ It is precipitated and separated in the form of Fe(OH)3 to obtain a leachate.

[0033] Step 4: Evaporation, cooling and crystallization: Take the leachate from step 3 and place it in a beaker. Heat it in a heating device to evaporate it. After evaporation, the specific gravity of the solution is controlled at 1.60-1.80 g / cm 3 , use external circulating cooling water for cooling, and the cooling crystallization end point is room temperature 25-28°C; the cooled solution is separated by a centrifuge, and the precipitate after centrifugal separation is microwave dried. The upper limit of the microwave drying temperature is 45°C, that is, dry at 45°C for 30-60s and then cool for 2min to obtain copper sulfate pentahydrate crystals.

[0034] Preferably, the mass fraction of the sulfuric acid solution in step 1 is 15%-30%.

[0035] Preferably, the quality of the copper sulfate pentahydrate crystals prepared in step 4 reaches the industry standard YS / t94-2007 first-class product.

[0036] The present invention does not particularly limit the sources of reagents used in the preparation process of copper sulfate pentahydrate crystals, and commercially available products well known to those skilled in the art can be used.

[0037] The present invention does not impose any particular limitation on the instruments used in the preparation process of copper sulfate pentahydrate crystals, and any experimental instruments commonly used by those skilled in the art may be used.

[0038] The invention adopts a high-temperature ventilation pressurized oxidation-acid leaching-evaporation-cooling crystallization-microwave drying combined method, which can leach copper ions in copper slag in a very short time without introducing new impurity particles, can reduce the consumption of concentrated sulfuric acid and the corrosion of equipment, and reduces the use of the difference in pH value of heavy metal ion precipitation to successfully separate it from copper ions in the solution, and then controls the specific gravity of the evaporated liquid and the cooling temperature to evaporate, cool and crystallize the purified liquid to obtain high-quality copper sulfate pentahydrate crystals.

[0039] The process flow chart of the present invention for preparing copper sulfate pentahydrate crystals using copper-rich slag is as follows: Figure 1 shown.

[0040] The copper-rich slag used in the embodiment of the present invention is a by-product produced during the smelting process of a non-ferrous metal smelting enterprise, and contains more than 20wt% copper. The contents of valuable metals such as zinc, lead, iron, silver, antimony, and bismuth in the copper slag are respectively in the range of 1 to 15wt%. In addition, the contents of sulfur and silicon dioxide are less than 1.0wt%. Phase analysis of the copper contained therein shows that the mass percentage of oxidized copper is 16.87%, and the mass percentage of sulfide copper is 11.70%.

[0041] The present invention is further described below by way of examples.

[0042] Example 1

[0043] Step 1, high temperature ventilation pressurized oxidation acid leaching: weigh 120g of copper-rich slag, crush the copper-rich slag and add it to a 15% sulfuric acid solution to dissolve it, the mass ratio of sulfuric acid solution to copper-rich slag is 2.5:1, introduce air and pressurize it to 0.5MPa, raise the temperature to 200℃ and carry out acid leaching reaction for 25min to make the metal Cu 2+ 、Zn 2+ 、Part of Cd 2+ , Fe 3+ , Fe 2+ 、Co 2+ , Sb 3+ , part Bi 3 + , Ca 2+ The plasma enters the sulfuric acid solution.

[0044] Step 2, filtration: After cooling the reaction device in step 1 using external circulating cooling water, the slurry in step 1 is taken out and vacuum filtered using a vacuum pump to obtain purified filtrate and leached residue, which is then further recovered and processed. The copper leaching rate is 95.3%.

[0045] Step 3, impurity removal: add slaked lime to the filtrate obtained in step 2, adjust the solution pH to 4.0, and make Fe 3+ It is precipitated and separated in the form of Fe(OH)3 to obtain a leachate.

[0046] Step 4: Evaporation cooling crystallization: Take 300 mL of the leachate from step 3 in a beaker and heat it to 95°C in a heating device for evaporation. After evaporation, the specific gravity of the solution is controlled at 1.69 g / cm 3 , use external circulating cooling water to cool down, and the cooling crystallization end point is room temperature 25°C; the cooled solution is separated by a centrifuge, and the separated precipitate is microwave dried (dried at a temperature of 45°C for 30s) and then cooled for 2min to obtain copper sulfate pentahydrate crystals.

[0047] The indicators of copper sulfate pentahydrate and impurities prepared in this embodiment are shown in Table 1. As can be seen from Table 1, the quality of the copper sulfate pentahydrate crystals prepared in this embodiment reaches the first-class product of the industry standard YS / t94-2007.

[0048] Table 1

[0049]

[0050] Example 2

[0051] Step 1, high temperature ventilation pressurized oxidation acid leaching: weigh 160g of copper-rich slag, crush the copper-rich slag and add it to a 20% sulfuric acid solution to dissolve it, the mass ratio of sulfuric acid solution to copper-rich slag is 3:1, introduce air and pressurize it to 0.7MPa, raise the temperature to 220℃ and carry out acid leaching reaction for 20min to make the metal Cu 2+ 、Zn 2+ 、Part of Cd 2+ , Fe 3+ , Fe 2+ 、Co 2+ , Sb 3+ , part Bi 3+ , Ca 2+ The plasma enters the sulfuric acid solution.

[0052] Step 2, filtration: Use external circulating cooling water to cool the reaction device in step 1, take out the slurry in step 1, and use a vacuum pump to vacuum filter to obtain purified filtrate and leached residue, which is then further recycled. The copper leaching rate is 96.8%.

[0053] Step 3, impurity removal: add slaked lime to the filtrate obtained in step 2, adjust the solution pH to 4.5, and make Fe 3+ It is precipitated and separated in the form of Fe(OH)3 to obtain a leachate.

[0054] Step 4: Evaporation cooling crystallization: Take 300 mL of the leachate from step 3 in a beaker and heat it to 98°C in a heating device for evaporation. After evaporation, the specific gravity of the solution is controlled at 1.71 g / cm 3, use external circulating cooling water to cool down, and the cooling crystallization end point is room temperature 26°C; the cooled solution is separated by a centrifuge, and the precipitate after centrifugal separation is microwave dried at a microwave drying temperature of 45°C and a time of 40s. After microwave drying, cool for 2 minutes to obtain copper sulfate pentahydrate crystals.

[0055] The indicators of copper sulfate pentahydrate and impurities prepared in this embodiment are shown in Table 2. As can be seen from Table 2, the quality of the copper sulfate pentahydrate crystals prepared in this embodiment reaches the industry standard YS / t94-2007 first-class product.

[0056] Table 2

[0057]

[0058] Example 3

[0059] Step 1, high temperature ventilation pressurized oxidation acid leaching: weigh 200g of copper-rich slag, crush the copper-rich slag and add it to a 25% sulfuric acid solution to dissolve it, the mass ratio of sulfuric acid solution to copper-rich slag is 3.5:1, introduce air and pressurize it to 0.8MPa, raise the temperature to 250℃ and carry out acid leaching reaction for 35min to make the metal Cu 2+ 、Zn 2+ 、Part of Cd 2+ , Fe 3+ , Fe 2+ 、Co 2+ , Sb 3+ , part Bi 3 + , Ca 2+ The plasma enters the sulfuric acid solution.

[0060] Step 2, filtration: Use external circulating cooling water to cool the reaction device in step 1, take out the slurry in step 1, and use a vacuum pump to vacuum filter to obtain purified filtrate and leached residue, which is then further recycled. The copper leaching rate is 97.8%.

[0061] Step 3, impurity removal: add slaked lime to the filtrate obtained in step 2, adjust the solution pH to 5.0, and make Fe 3+ It is precipitated and separated in the form of Fe(OH)3 to obtain a leachate.

[0062] Step 4: Evaporation cooling crystallization: Take 300 mL of the leachate from step 3 in a beaker and heat it to 100 °C in a heating device for evaporation. After evaporation, the specific gravity of the solution is controlled at 1.77 g / cm 3, use external circulating cooling water to cool down, and the cooling crystallization end point is room temperature 27°C; the cooled solution is separated by a centrifuge, and the precipitate after centrifugal separation is microwave dried at a microwave drying temperature of 40°C for 60s. After microwave drying, cool for 2min to obtain copper sulfate pentahydrate crystals.

[0063] The indicators of copper sulfate pentahydrate and impurities prepared in this embodiment are shown in Table 3. As can be seen from Table 3, the quality of the copper sulfate pentahydrate crystals prepared in this embodiment reaches the first-class product of the industry standard YS / t94-2007.

[0064] Table 3

[0065]

[0066] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing copper sulfate pentahydrate crystals using copper-rich slag, characterized in that: The following steps are involved: The copper-rich slag is added to a sulfuric acid solution and pressurized to carry out an acid leaching reaction, and then the temperature is reduced and filtered to obtain a filtrate; adding slaked lime to the filtrate to separate and obtain a leachate; The leachate is evaporated, then cooled for crystallization, and centrifuged, and the precipitate obtained by centrifugation is microwave dried to obtain the copper sulfate pentahydrate crystals.

2. The method for preparing copper sulfate pentahydrate crystals using copper-rich slag according to claim 1, characterized in that: The copper-rich slag is a by-product produced during the non-ferrous metal smelting process.

3. The method for preparing copper sulfate pentahydrate crystals using copper-rich slag according to claim 1, characterized in that: The mass concentration of the sulfuric acid solution is 15%-30%; the mass ratio of the sulfuric acid solution to the copper-rich slag is (2-4):1; the pressurization is specifically to introduce air to pressurize 0.5-1.0MPa; the temperature of the acid leaching reaction is 200-300°C, and the time is 20-40min.

4. The method for preparing copper sulfate pentahydrate crystals using copper-rich slag according to claim 1, characterized in that: The cooling is specifically cooling by circulating cooling water.

5. The method for preparing copper sulfate pentahydrate crystals using copper-rich slag according to claim 1, characterized in that: The amount of slaked lime added is such that the pH of the filtrate is 4.0-5.

0.

6. The method for preparing copper sulfate pentahydrate crystals using copper-rich slag according to claim 1, characterized in that: The specific gravity of the leaching solution is controlled to be 1.6-1.8 g / cm by evaporation. 3 ; The cooling crystallization is specifically cooling to room temperature by circulating cooling water.

7. The cupric sulfate pentahydrate crystal prepared according to the method described in any one of claims 1 to 6.

8. Application of the copper sulfate pentahydrate crystal as claimed in claim 7 in industrial fields, agricultural fields or chemical analysis fields.